Pengaruh Kredit Perbankan Terhadap Pertumbuhan Ekonomi Provinsi di Sumatera - Rhisca Meci Lestari; Ratu Eva Febriani; Novi Tri Putri (Universitas Bengkulu, 2021)
The purpose of this study was to analyze working capital loans, investment loans and consumption loans in Sumatra Province in 2010-2018. This type of research used in this study is secondary data, namely data in the form of numbers or quantitative time series. Based on the results of the panel analysis of regression data by E-Views 9, working capital credit are positive and significant to economic growth in Provinces in Sumatra, investment credit is positive and significant to economic growth in Provinces in Sumatra and consumption credit have positive and significant income to economic growth in the Provinces all over Sumatra. Keywords: Working capital credit1, Investment credit2, Consumption credit3, Economic growth4